Analisis Perbandingan Merek Smartphone Apple dan Samsung pada Mahasiswa Fakultas Ekonomi Universitas Swasta di Jakarta - Susbiyantoro; Caroline; Aninam, Johny; Nugraha, Aat Ruchiat (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The rapid development of the telecommunications sector, especially the smartphone sector, has created fierce competition among different brands to win the hearts of consumers. This study aimed to determine the differences in brand associations between the two market leaders, Apple iPhone, and Samsung, among students of the Faculty of Economics of a private university in Jakarta. Data was collected through a survey of 100 respondents who have used or are currently using products from one of these brands. Data analysis results show a significant difference in brand associations between Apple iPhone and Samsung. The high t value (9.296 > 1.984) confirms that this difference is statistically significant. These results provide valuable information about how these two brands are perceived by students in the School of Economics, which can be used to improve branding and marketing strategies within a market. growing and more competitive. This study makes an important contribution to understanding the dynamics of brand associations in the context of the rapidly evolving smartphone industry.